Non-tuberculous mycobacteria isolated at the end of the world - Ferrara Muñiz, Ximena; Tortone, Claudia Andrea; Oriani, Delia Susana; Garro, Carlos Javier; Garbaccio, Sergio Gabriel; Farace, Pablo Daniel; Encinas, Micaela; Eirin, Maria Emilia; Zumarraga, Martin Jose (European Society of Mycobacteriology, 2024)
Poster